Current status of CTV in new plantation of citrus in Layyah and Bhakkar, Pakistan - Shafique, Talha; Anum, Sara; Iftikhar, Yasir; Shakeel, Qaiser; Zeshan, Muhammad Ahmad; Khan, Javaid; Zafar, Muhammad Irfan; Riaz, Talha; Saeed, Muhammad Hamza; Safdar, Rabia; Ali, Imran (Journal of Agriculture and Biology, 2024)
Citrus fruit is widely regarded as a valuable commodity on a global scale, especially within the country of Pakistan, due to its great flavor, nutritional advantages, and therapeutic attributes. The Citrus Tristeza Virus (CTV) is a significant pathogen that poses a substantial threat to the citrus industry's stability and productivity. The tree that has been impacted by the disease displays symptoms of deterioration, including leaf chlorosis, twigs dieback, and stem pitting. The objective of this study was to document the occurrence and severity of CTV disease using symptomatology and serological studies. A survey was conducted in two districts of Punjab named as District Bhakkar and Layyah. This research carried out in each district included identification of seven sample agricultural fields and the evaluation of three types of citrus fruits including Musambi, Feutral’s Early and Kinnow. Serological test known as ELISA was used for an analysis of the samples that were suspected to contain CTV. The study was observed that the extent of the condition was present in all the regions. The study also shows that among the sites, identified the Musambi was the most affected by the climatic change, trailed by Feutral and Kinnow respectively. Similarly District Layyah presented higher disease severity as compared to the District Bhakkar. The study shows that the level of disease incidence in orchards increases with the age of CTV in a given orchard. Future research should explore efficient strategies for controlling CTV disease, including cultivar resistance through gene silencing and examine the economic impact on citrus businesses in Pakistan and other countries.
Keywords: Citrus Tristeza Virus; ELISA; new plantation; Layyah; Bhakkar